TASUM-R model: Basic techniques of recurve archery - Husin, M. R.; Txi, M. R. S.; Salleh, F. N. M.; Aziz, A. K. A. (International Journal of Research in Education Humanities and Commerce, 2023)
Archery requires a high concentration of learning and practicing the right techniques. The technique in archery sports requires the same repetition each time to get the same result. The analysis of the results of the MSSPK Recurve Archery Championship 2022 Circuit 2 recorded that only 30% of participants scored more than half for each end i.e. 180 out of 360 scores. This data shows that most participants are unable to consistently release arrows and are accurate on the target board. Consistency and accuracy are important factors in archery. Both of these factors can be enhanced through effective techniques as well as high concentration. Therefore, the TASUM-R model will be developed as a guideline for coaches and archer athletes to enhance the effectiveness of both factors, thus enabling participants to score more than 180, and even achieve 300 points for 6 ends in 3 months of training alone compared to 6 months or more previously. This study used the DDR design to produce the TASUM-R model, which is the Basic Technique of Recurve Archery Sports. This innovation collaborates with an industry partner, Team Freedah Archerz for the purpose of exposure to archery sports enthusiasts from childhood to adulthood as well as the corporatization of a complete module based on the TASUM-R Model.